Directive Speech Acts by Child Characters in the Japanese Film Monster (2023): A Pragmatic Analysis - Gading, Erland Rakarussi; Kasmawati, Kasmawati (NAWA: Journal of Japanese Studies, 2026)
This study investigates the forms and types of directive speech acts produced by child characters in the Japanese film Monster (2023) directed by Hirokazu Koreeda. Using a qualitative approach, the study analyzes 20 directive utterances drawn from the film’s dialogue to examine how directive meanings are realized in emotionally and socially complex interactions. The data were selected by identifying utterances spoken by child characters that pragmatically function to prompt the addressee to perform or refrain from performing an action. The analysis is informed by speech act theory and contextual interpretation through Dell Hymes’ SPEAKING framework, enabling systematic examination of linguistic form, pragmatic function, and interactional context. The findings reveal that directive speech acts are realized through direct and indirect as well as literal and non-literal forms. Among these, indirect literal directive speech acts of the requestive type occur most frequently. This pattern indicates that directive intentions are commonly conveyed through interrogative or declarative structures rather than explicit imperatives, particularly in emotionally sensitive interactions such as family communication and peer relationships affected by bullying. Overall, the study demonstrates that child characters exhibit pragmatic awareness by employing directive strategies that balance communicative effectiveness with interpersonal consideration.